Diagnóstico da fertilidade do solo de áreas em implantação de agricultura de precisão no Rio Grande do Sul - Dias, Rodrigo Franco (2013)
This study sought to describe the current state fertility levels by analyzing 105,342 soil samples from different regions of the state of Rio Grande do Sul assigned by CCGL Technology. Thus, about 42% of the samples need to correct soil acidity. Phosphorus was the element that needs more attention in the soil correction. Potassium is present in most samples above the critical level suggesting a poor response to application in current models. Correction sulfur has potential response to crop yields in soya. In a second step, we used the data to study the balance of nutrients in the soil. The data were normalized and CTCpH7,0 was the parameter of soil divided into classes considering the normal distribution with a standard deviation for each class. The results showed that the base saturation to achieve the desired pH varied according to CTCpH7,0v soil. Soils with low CTCpH7,0 present trend lower percentage base saturation than a soil with CTCpH7,0 high. It was also found that the CTCpH7,0 soil influences the availability of the potassium equilibrium saturation. Soils with higher CTCpH7,0 require larger amounts of potassium to reach the critical level of 3% CTCpH7,0. The next step was to correlate the levels of elements in the soil and its relation to the levels shown by leaf analysis. For that were conducted soil sampling in grid 2 ha in an area in the municipality of Cachoeira do Sul, RS. This area was located soybean and collected samples of leaves and plants when they were in the flowering stage in the same spots where they were taken soil samples. Reading was also performed with the equipment GreenSeeker order to correlate them with samples of soil and leaves.The CTCpH7,0 soil, directly influences the availability of potassium in equilibrium saturation. Soils with higher cation exchange capacity tend to require larger amounts of potassium to reach the critical level of 3% of CTCpH7,0. The results of tissue samples of whole plants soybean correlate with the levels of potassium in the soil and its percentage in CTCpH7,0. Nevertheless the use of the analysis of the 3rd trifoliate leaf from flowering as a parameter for recommendation requires further study, as the results do not make clear the relationships between these elements in the leaves and in the soil.